Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/112067210801800512
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Visual Acuity without Spectacles following Bilateral ReSTOR® Implantation

Abstract: In an everyday surgical practice, none of the studied bilateral ReSTOR cataract patients without astigmatism required spectacles when followed up 6 months or later. Intermediate VA was compatible with reading and led to high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, advances in surgical techniques, IOL designs and biometry are maximising the potential of correction of toric IOLs 3 20. Hirnschall et al 21 showed in a comparative study of 60 eyes of 30 patients that toric IOLs could reduce astigmatism to a higher extent, and were more predictable than peripheral corneal relaxing incisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in surgical techniques, IOL designs and biometry are maximising the potential of correction of toric IOLs 3 20. Hirnschall et al 21 showed in a comparative study of 60 eyes of 30 patients that toric IOLs could reduce astigmatism to a higher extent, and were more predictable than peripheral corneal relaxing incisions.…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate and near vision were measured using the SLOAN Two-Side EDTRS Format Near Vision Chart (Precision Vision, La Salle, IL). The actual VA in logarithm of the minimum angle of resolution at its corresponding distance was calculated by the visual angle subtended for statistical analyses [3, 4, 25]. The CS was recorded using the CSV-1000E (Vector Vision, Greenville, OH).…”
Section: Methodsmentioning
confidence: 99%
“…For intermediate visual acuities at 2 m, 1 m, and 70 cm and for near visual acuities at 50 cm and 33 cm, scales were corrected accordingly as previously described. 25 Logarithmic scales were used for statistical and graphical purposes with regard to contrast sensitivity data. Manifest refractions were converted into power vector coordinates as proposed by Thibos and Horner.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%